GE_GERICHTE C/20339/2011 vom 29. August 2014 - GE Cour de justice (2014)
BANQUE; GESTION DE FORTUNE; ACTION EN RESPONSABILITÉ; OBLIGATION DE RENSEIGNER | CO.33.3; CO.394; CO.398.2; CO.425; CO.436; LBVM.11